Protection of the personal data by data masking method - Коломицев, Михайло Володимирович; Южаков, Анатолій Михайлович (Ukrainian Information Security Research Journal, 2013)
In accordance to a law on the protection of the personal data, proprietors of bases of the personal information are under an obligation to provide their defence. By the basic type of depository for the personal information there is a database in the informative system. Practice of development of the informative systems shows that except for a productive (basic) database there is a task of creation of its copies, unproductive (test) databases. To use such universal mechanism in test databases, as cryptography, for the protection of the personal data is not always possible. Reason to that not only the known legislative limitations but also that test databases must be functionally equivalent a production database. It means that the protected information must be presented in a kind, not defiat integrity of database (both integrity on references and on belonging of information to the certain domain). For the protection of the personal data it is possible to take approach in such situation, which is named data masking method. Essence of this method, his actuality, requirements to realization, opens up in this article. Authors offer developed by them as a programming code of protection of the personal data in the environment of MS SQL Server.